2022
DOI: 10.1111/apa.16401
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth rates were slightly lower in Denmark during the first year of the COVID‐19 pandemic compared with the previous 4 years

Abstract: Aim Our aim was to investigate the rates of preterm births, live births and stillbirths in Denmark during the first year of the COVID‐19 pandemic. Methods This was a national, cross‐sectional registry‐based study that used the Danish Newborn Quality database, which covers all births in Denmark. The proportions of preterm births were compared between the COVID‐19 pandemic period of 1 March 2020 to 28 February 2021 and the preceding 4‐year pre‐pandemic period. Results We studied 60 323 and 244 481 newborn infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
3
16
1
Order By: Relevance
“…If it is accepted that Norway did not experience a reduction in xPTBs 3 , assuming a 10 % proportion of multifetal xPTB pregnancies, then the Danish reduction of singleton xPTBs pregnancies over a three-month period can be estimated to be ~ 40 %. Clearly compatible with the 73 % (95% CI, 14 % - 93 %) reduction in xPTBs found in the Danish National Patient Register based study on all Danish singleton preterm births 1 , and the 56 % and 47 % reductions in xPTBs in March and April 2020 reported in a study based on data from the Danish Newborn Quality Database 5 .…”
Section: Tablesupporting
confidence: 81%
See 2 more Smart Citations
“…If it is accepted that Norway did not experience a reduction in xPTBs 3 , assuming a 10 % proportion of multifetal xPTB pregnancies, then the Danish reduction of singleton xPTBs pregnancies over a three-month period can be estimated to be ~ 40 %. Clearly compatible with the 73 % (95% CI, 14 % - 93 %) reduction in xPTBs found in the Danish National Patient Register based study on all Danish singleton preterm births 1 , and the 56 % and 47 % reductions in xPTBs in March and April 2020 reported in a study based on data from the Danish Newborn Quality Database 5 .…”
Section: Tablesupporting
confidence: 81%
“…Three subsequent studies, which included Danish data, all examined PTB rates without excluding multifetal pregnancies 3-5 . This makes data interpretation difficult, as multifetal pregnancies have a different set of risk factors for PTB, increased risk of adverse outcome, and a shorter expected pregnancy length.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a recent study reported slightly lower preterm birth rates in Denmark during the first year of the COVID‐19 pandemic compared with the previous 4 years. 5 In addition to high body mass index, advanced maternal age and non‐white ethnic origin, evidence suggests that pre‐existing comorbidities and pregnancy‐specific conditions such as preeclampsia and gestational diabetes are risk factors for severe disease. 4 At the same time, COVID‐19 has increased the incidence of preeclampsia and hypertensive disorders of pregnancy, stillbirths, perinatal mortality and Caesarean deliveries, which should only be performed for standard obstetric indications.…”
Section: Impact On Pregnancy and The Placentamentioning
confidence: 99%
“…Most attention has been paid to the impact of the pandemic on preterm birth (PTB), but with inconsistent results. Reductions in PTB rates during COVID-19 pandemic compared with before pandemic have been reported in many countries, such as Australia ( 10 12 ), the United States ( 13 15 ), Israel ( 16 ), the Netherlands ( 17 ), Denmark and Ireland ( 18 20 ), while studies in China, Sweden and Spain have not found such changes ( 21 23 ). In a recent meta-analysis, PTB was not significantly changed overall but was decreased in high-income countries ( 24 ).…”
Section: Introductionmentioning
confidence: 99%